Development of the Nagari Tuo Pariangan Tourist Village Based on Social Empowerment - Iswadi Iswadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The Nagari Tuo Pariangan Tourism Village, located in West Sumatra, is a village for the Minangkabau community as the origin of the growth of small villages in Minangkabau. Communities around the village generally work as farmers. Their source of income from farming and gardening makes the community quite prosperous and part of the population migrates. With the natural wealth of the people of Nagari Tuo Pariangan, they also empower their area as a leading tourism and cultural center, this is evidenced by statistics on the increase in visits every year. This development shows that the level of community participation in Nagari Tuo Pariangan has increased participation and has also experienced developments in other sectors, such as the economic life development sector, and the social sector in the community. From a level that only relies on rice fields and plantations, it has increased with an increase in the tourism. Describe the level of participation of the Nagari Parianagan Community in Empowerment as a Natural and Cultural Tourism Village. To do this research, the methodology used is qualitative by exploring all sources of library data for research. The results show that the level of community participation in Nagari Tuo Pariangan has increased, especially in the form of partnerships so that there is an increase in community empowerment in the Natural and Cultural Tourism Village.